2003
DOI: 10.1037/0033-2909.129.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Transformational, transactional, and laissez-faire leadership styles: A meta-analysis comparing women and men.

Abstract: A meta-analysis of 45 studies of transformational, transactional, and laissez-faire leadership styles found that female leaders were more transformational than male leaders and also engaged in more of the contingent reward behaviors that are a component of transactional leadership. Male leaders were generally more likely to manifest the other aspects of transactional leadership (active and passive management by exception) and laissez-faire leadership. Although these differences between male and female leaders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

69
1,517
21
84

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,825 publications
(1,691 citation statements)
references
References 122 publications
69
1,517
21
84
Order By: Relevance
“…Male supervisors often use transactional leadership behaviors, and in particular punishing errors [21]. In these instances, the supervisor is actively monitoring the performance of the employee and takes action when an error occurs [22].…”
Section: Factors Affecting Motivation To Collect High Quality Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Male supervisors often use transactional leadership behaviors, and in particular punishing errors [21]. In these instances, the supervisor is actively monitoring the performance of the employee and takes action when an error occurs [22].…”
Section: Factors Affecting Motivation To Collect High Quality Datamentioning
confidence: 99%
“…This theory suggests that transactional leadership behaviors (including punishing errors and rewarding performance) operates as a foundation on which transformational leadership behaviors (including inspirational communication, consideration of each individual employee's needs, charisma, and intellectual stimulation) build. Considerable research has shown that each of these components are significantly related to leadership effectiveness [20].Male supervisors often use transactional leadership behaviors, and in particular punishing errors [21]. In these instances, the supervisor is actively monitoring the performance of the employee and takes action when an error occurs [22].…”
mentioning
confidence: 99%
“…Compared with men, women have similar leadership aspirations 11,12 and are at least as effective as leaders. [13][14][15] Yet equity has not been attained.…”
mentioning
confidence: 99%
“…Transactional leaders appeal to a supervisee's self-interest through exchange relationships, which involves managing, rewarding and correcting (Eagly and Johannesen-Schmidt, 2003).…”
Section: Are Administrative and Educative Functions Of Supervision Comentioning
confidence: 99%
“…Transformational leadership involves inspiring and nurturing supervisees by acting as a role model, clearly articulating future goals, mentoring and empowering (Eagly and Johannesen-Schmidt, 2003).…”
Section: Are Administrative and Educative Functions Of Supervision Comentioning
confidence: 99%